2022
DOI: 10.1186/s13578-022-00839-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel and atypical NF-KB pro-inflammatory program regulated by a CamKII-proteasome axis is involved in the early activation of Muller glia by high glucose

Abstract: Background Diabetic retinopathy (DR) is a microvascular complication of diabetes with a heavy impact on the quality of life of subjects and with a dramatic burden for health and economic systems on a global scale. Although the pathogenesis of DR is largely unknown, several preclinical data have pointed out to a main role of Muller glia (MG), a cell type which spans across the retina layers providing nourishment and support for Retina Ganglion Cells (RGCs), in sensing hyper-glycemia and in acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Recently, RNA-Seq analysis and experiments indicated that TMZ inhibited cell apoptosis by downregulating the calmodulin-dependent protein kinase II (CaMK II) pathway after myocardial infarction, 30 whereas in the early activation of Muller glia by high glucose, the induction of an early and atypical NF-κB signaling pathway regulated by CaMK II has been reported. 31 Combined with the evidence of ROS-mediated CaMKII activation, 32 these findings implied a likely ROS/CaMKII/NF-κB apoptosis signaling pathway regulated by TMZ, which may explain the above findings.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, RNA-Seq analysis and experiments indicated that TMZ inhibited cell apoptosis by downregulating the calmodulin-dependent protein kinase II (CaMK II) pathway after myocardial infarction, 30 whereas in the early activation of Muller glia by high glucose, the induction of an early and atypical NF-κB signaling pathway regulated by CaMK II has been reported. 31 Combined with the evidence of ROS-mediated CaMKII activation, 32 these findings implied a likely ROS/CaMKII/NF-κB apoptosis signaling pathway regulated by TMZ, which may explain the above findings.…”
Section: Discussionmentioning
confidence: 82%
“…SOD2 expression can be regulated by a series of in ammatory cytokines, growth factors, and redox activators via transcriptional and post-transcriptional regulatory mechanisms (Zelko et al 2002). Activation of the NF-κB pathway is a key regulator of in ammation-related tumor progression, and H. pylori infection is thought to generate an in ammatory microenvironment by activating the NF-ĸB pathway (Shalapour and Karin 2015; Lamb et al 2009;Sbardella et al 2022). Our ndings revealed the transcriptional upregulation of SOD2 by NF-κB during H. pylori infection and con rmed crucial NF-κB binding sites in the SOD2 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…However, 48 hours of berberine treatment restored the rate of phosphorylated AMPK and mTOR, inducing autophagy and inhibiting apoptosis [67]. Nevertheless, the evidence that high glucose levels (typically > 25 mM) may impact the autophagy signaling cascade, but also the ubiquitin-proteasome system (UPS), has been envisaged by studies carried out in rMC1 cells, an immortalized strain of rat Müller cells [70,71]. In 2021, Wang and co-authors proposed that berberine improves the response of retinal endothelial cells to insulin treatment [72].…”
Section: Berberine An Isoquinoline Alkaloidmentioning
confidence: 99%